The mediated mind : affect, ephemera, and consumerism in the nineteenth century - Zieger, Susan Marjorie (New York : Fordham University Press, 2018)
This book describes new affective and material modes of print media consumption that emerged in the nineteenth century, when ephemeral printed material and objects became part of everyday modern life. It offers a history of our own moment of digital absorption, information addiction, and social media obsession.
Intro; Half Title; Title Page; Copyright; Contents; Introduction: From Paper to Pixel; 1. Temperate Media: Ephemera and Performance in the Making of Mass Culture; 2. Tobacco Papers, Holmes's Pipe, Cigarette Cards, and Information Addiction; 3. Ink, Mass Culture, and the Unconscious; 4. "Dreaming True": Playback, Immediacy, and "Du Maurierness"; 5. "A Form of Reverie, a Malady of Dreaming": Dorian Gray, Personality, and Mass Culture; Conclusion: Unknown Publics; Acknowledgments; Notes; Index.
Online resource; title from digital title page (viewed on June 05, 2018).
Includes bibliographical references (pages 219-259) and index.
JSTOR
Keywords: Mass media and literature; Mass media and culture; Mass media -- Social aspects -- History -- 19th century; Printed ephemera -- Social aspects -- History -- 19th century; Médias et littérature.; Médias et culture; Médias -- Aspect social -- Histoire -- 19e siècle.; Publications éphémères -- Aspect social -- Histoire -- 19e siècle.; SOCIAL SCIENCE -- Media Studies; Mass media and culture; Mass media and literature; Mass media -- Social aspects; Printed ephemera -- Social aspects; 1800-1899; Electronic books; History